2017
DOI: 10.1590/1983-21252017v30n207rc
|View full text |Cite
|
Sign up to set email alerts
|

Different Shading Environments Impact Growth and Yield of Three Mini-Tomato Cultivars

Abstract: -Our study was conducted in the experimental field of the Department of Technology and Social Sciences (DTCS) of the State University of Bahia -UNEB, Juazeiro-BA. The experimental design was comprised of randomized blocks, sub-subdivided in plots, with four replicates comprising the plots of three different shading methods, gray shading screen (GS), red shading screen (RS), and blue shading screen (BS), and the control treatment with no shading. The subplots comprised three mini-tomato cultivars ("Sweet Millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…In general terms, the agroclimatic results corroborate with Gama et al (2017), who working with shade screens for the production of cherry tomatoes in the same region of the present research, identified microclimatic changes in the environments, however, with greater changes for solar radiation, whereas, the average temperature did not vary in any way significant.…”
Section: Results and Discusionsupporting
confidence: 91%
“…In general terms, the agroclimatic results corroborate with Gama et al (2017), who working with shade screens for the production of cherry tomatoes in the same region of the present research, identified microclimatic changes in the environments, however, with greater changes for solar radiation, whereas, the average temperature did not vary in any way significant.…”
Section: Results and Discusionsupporting
confidence: 91%
“…It was due to higher shading level decreased sugar content of tomato fruit (Kirschbaum, 2011). The high temperature was well known to influence fruit maturity and growth (Gama et al, 2017). Besides, a previous study reported total sugar content in five genotypes of tomato.…”
Section: Yield Production and Qualitymentioning
confidence: 94%
“…As telas de coloração vermelha transferem mais a luz do espectro nas ondas vermelho e vermelho distante e difundem a luz que passa através da malha, sendo eficiente no desenvolvimento da planta (LI, 2006). Além disso, independente do fator de sombreamento, a malha vermelha proporciona maior transmitância de radiação fotossintéticamente ativa (RFA) para o interior do ambiente de cultivo (GAMA et al, 2017).…”
Section: Introductionunclassified